A collection of efficient tools to work with almost strictly sign regular matrices. Issue 6 (5th December 2021) - Alonso Velázquez, Pedro; Jiménez Meana, Jorge; Peña Ferrández, Juan Manuel; Serrano Ortega, María Luisa
Abstract: In this work, several algorithms have been implemented with Matlab to obtain an algorithmic characterizations of almost strictly sign regular matrices using Neville elimination.